1988
DOI: 10.1093/jnci/80.10.739
|View full text |Cite
|
Sign up to set email alerts
|

Combination Cytotoxic Chemotherapy With Cisplatin or Doxorubicin and Photodynamic Therapy in Murine Tumors1

Abstract: This study was designed to evaluate the interaction of photodynamic therapy (PDT) and chemotherapy in an animal model. PDT is based on the interaction of hematoporphyrin derivative and red light of the appropriate wavelength (630 nm) and intensity. Two tumor models were utilized: C3H/Km mice bearing the RIF-1 tumor and BALB/c mice bearing the EMT-6 tumor. Tumor-bearing mice were treated with either cisplatin (DDP), doxorubicin (ADM), PDT, or a combination of drug and PDT. It was demonstrated that the RIF-1 tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 0 publications
1
47
0
Order By: Relevance
“…Although combinations of PDT with other treatment modalities, such as X-irradiation (Bellnier & Dougherty, 1986;Winther et al, 1988;Levendag et al, 1989), chemotherapy using adriamycin (Edell & Cortese, 1988), cisplatin or doxorubicin (Nahabedian et al, 1988), hyperthermia by combining PDT with microwave irradiation (Waldow & Dougherty, 1984;Waldow et al, 1987;Levendag et al, 1989) and the use of hypoxic cell sensitisers, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although combinations of PDT with other treatment modalities, such as X-irradiation (Bellnier & Dougherty, 1986;Winther et al, 1988;Levendag et al, 1989), chemotherapy using adriamycin (Edell & Cortese, 1988), cisplatin or doxorubicin (Nahabedian et al, 1988), hyperthermia by combining PDT with microwave irradiation (Waldow & Dougherty, 1984;Waldow et al, 1987;Levendag et al, 1989) and the use of hypoxic cell sensitisers, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The typical clinical PDT protocol consists of the systemic administration of 2-5 mg kg-' Photofrin 11 followed 24-72 h later by exposure of malignant lesions to 50-400 J cm-2 visible photoradiation, usually 630 nm laser emission. Utilising these treatment conditions for various types of malignancies, encouraging clinical results have been reported (Kato et al, 1986;Lam et al, 1987;Gilson et al, 1988;Nseyo et al, 1987;McCaughan et al, 1988). Any improvement in the efficacy of PDT should increase its acceptance as a useful cancer treatment.…”
mentioning
confidence: 99%
“…The addition of mitomycin C has been shown to enhance the PDT effect (Nahabedian et al, 1988). Recently, it has been reported that loss of MMR is specifically associated with hypersensitivity to mitomycin C (Fiumicino et al, 2000).…”
Section: Molecular and Cellular Pathologymentioning
confidence: 99%
“…For example, combinations of chemotherapies using agents with different mechanisms of action (Harris et al, 2005;Shanks et al, 2005); chemotherapy in combination with photodynamic therapy (PDT) (Nahabedian et al, 1988;Jin et al, 1992;Peterson et al, 1995); chemotherapy and immunotherapy (Welt et al, 2003); PDT and radiotherapy (Colasanti et al, 2004); and radioimmunotherapy with radiotherapy (Buchegger et al, 2000) have been studied.…”
Section: Introductionmentioning
confidence: 99%